Proctor cone penetrometer for in-situ soil strength studies in Nigeria - Ani, Anthony Ozoemena; Mbajiorgu, Constantine C.; Akubuo, Clement Onyeaghala; Onwualu, Peter Azikiwe (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: Investigations of in-situ or laboratory soil strength properties, particularly the resistance of soil to penetration, usually referred to as cone index (CI) are often required in soil tillage and traction studies. ?This helps in the analysis of the interactions of both tillage tools and tractive elements with the soil. ?However, penetrometer, the instrument used for measuring this important parameter (CI), is not readily available in Nigeria. ?Following the recommendations in ASAE standards, a functional proctor cone penetrometer for soft soils has been developed and calibrated. ?The major parts include the handle, made of half-inch galvanized pipe, constructed in such a way that it can be screwed on and off the pressure shaft conveniently, the graduated pressure and penetration shafts made of stainless steel; the spring loaded pressure chamber, and a cone probe. ?The penetrometer was calibrated by applying known forces on the handle while noting corresponding penetrations and displacements on the graduated pressure shaft. ?A performance test was carried out on a clayey loam soil to compare the readings obtained from the developed penetrometer and an imported one. ?The major difference between the two is that while one is very expensive and scarce to come by, the other is produced locally with locally sourced materials and technology. ?The cost of the imported one is ten times more than that of the local one. ?The mean CI obtained for twenty-four random samples on the soil surface for the test area at 18 cm depth was found to be 1.4358 MPa for the local, and 1.5096 MPa for the imported.? Regression analysis of the two sets of values of CI for the local and the foreign showed a strong correlation (R2 = 0.779, P<0.05). ?This implies that the locally produced proctor penetrometer is reliable for measurements of CI at 0